Visualizing Africa in nineteenth-century British travel accounts [ - Koivunen, Leila (Routledge research in travel writing, 2009)
Examines and explains how British explorers visualized the African interior in the latter part of the nineteenth century, providing an analysis of the process by which this visual material was transformed into the illustrations in popular travel books